Lactic acid bacteria profile of Capiz, Philippines water kefir grains in a three-level propagation scheme - Chavez, Arian B.; Azanza, Ma. Patricia V. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
The present study established the lactic acid bacteria profile of water kefir grains obtained from Capiz, Antique, Philippines in 5% brown sugar solution (30±2°C) using a three-level propagation scheme. Dried kefir grains were evaluated to have the following characteristics:131 U to Black 4 U Pantone® color range, 2.4-6.9 mm in diameter grain size, 0.766 Aw and 11.06% moisture content(dry basis). The mean APC, MPC, LAB count and YC values were 5.15 log cfu/g, 6.44 log cfu/g,3.80 log cfu/g and 4.97 log cfu/g, respectively. The detectable microbial counts despite the dry state of the kefir grains were attributed to the protection provided by the polysaccharide encapsulating the microorganisms in the dried kefir grains. The maximum hydrated state of the kefir was achieved after 12-24 h time interval of activation in 5% brown sugar solution. The decrease in APC and the MPC of water kefir grains across 3-level propagation was attributed to the dispersal of microorganisms into the supernatant. The increase in LAB counts of water kefir grains across the 3-level propagation along with the increase in biomass was explained to be due to the reproduction of LAB during the step. Most of the microorganisms in the kefir grains tend to be dispersed into the supernatant inoculated with the kefir grains used in the study while the LAB showed strong adherence onto the kefir grain matrix at the 3rd level propagation. About 60%-80%of the microbial isolates were identified to be Lactobacillus spp. based on morphological and biochemical tests conducted. It was recommended that validation and further studies on the physical and microbiological characteristics of the water kefir grains be conducted to fully establish its properties.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Kefir -- Philippines -- Capiz; Water kefir grains; Lactic acid bacteria